Saturday

August 23, 2014

August 23, 2014

Posted by **Allessandra** on Saturday, December 17, 2011 at 12:50am.

(1- sinx) / (1 +sinx)

How would I do this?

The answer is (-2cosx)/ (1 + sinx)^2

Thanks in advance :)!!

- Math -
**Steve**, Saturday, December 17, 2011 at 6:05amd/dx (1-sinx)/(1+sinx)

[-cosx (1+sinx) - (1-sinx)(cosx)]/(1+sinx)^2

(-cosx - sinx cosx - cosx + sinx cosx)/(1+sinx)^2

= -2cosx/(1+sinx)^2

**Related Questions**

Trig Help - Prove the following: [1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx...

math - tanx+secx=2cosx (sinx/cosx)+ (1/cosx)=2cosx (sinx+1)/cosx =2cosx ...

math - the problem is 2cos^2x + sinx-1=0 the directions are to "use an identity ...

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

trigonometry - can i use factoring to simplify this trig identity? the problem ...

math - solve each equation for 0=/<x=/<2pi sin^2x + 5sinx + 6 = 0? how do ...

check math - Here are my answers. Can you check if I got the right answers? ...

Trig - prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= ...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...